Longitudinal change in collagen degradation biomarkers in idiopathic pulmonary fibrosis: an analysis from the prospective, multicentre PROFILE study - Jenkins, R. Gisli; Simpson, Juliet K.; Saini, Gauri; Bentley, Jane H.; Russell, Anne-Marie; Braybrooke, Rebecca; Molyneux, Philip L.; McKeever, Tricia M.; Wells, Athol U.; Flynn, Aiden; Hubbard, Richard B.; Leeming, Diana J.; et al. (Elsevier, 2015)
BACKGROUND: Idiopathic pulmonary fibrosis, a progressive and inevitably fatal disorder, has a highly variable clinical course. Biomarkers that reflect disease activity are urgently needed to inform patient management and for use as biomarkers of therapeutic response (theragnostic biomarkers) in clinical trials. We aimed to determine whether dynamic change in markers of extracellular matrix (ECM) turnover predicts progression of idiopathic pulmonary fibrosis as determined by change in forced vital capacity and death.